2018
DOI: 10.1111/luts.12219
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term results of changes in existing and de novo lower urinary tract symptoms after robot‐assisted laparoscopic uterosacral ligament suspension and sacrocolpopexy

Abstract: Mixed incontinence and pelvic pain improved significantly in patients after RALUSLS or RALSC. In RALUSLS patients, urgency, frequency, and urge incontinence also improved, whereas additional improvement in nocturia and dyspareunia was evident only in RALSC patients. De novo LUTS developing after these procedures, especially after RALSC, necessitate careful patient consultation prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Loss of apical support is usually present in patients with prolapse, and sufficient support for the vaginal apex is a crucial component of an enduring surgical treatment. [ 5 ] Laparoscopic sacrocolpopexy and sacrohysteropexy (uterus preserving sacrocolpopexy) have been demonstrated to be effective surgical techniques in apical prolapse treatment. [ 6 ] They provide good apical support.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of apical support is usually present in patients with prolapse, and sufficient support for the vaginal apex is a crucial component of an enduring surgical treatment. [ 5 ] Laparoscopic sacrocolpopexy and sacrohysteropexy (uterus preserving sacrocolpopexy) have been demonstrated to be effective surgical techniques in apical prolapse treatment. [ 6 ] They provide good apical support.…”
Section: Introductionmentioning
confidence: 99%
“…In our study the patient satisfaction related to urinary and bowel complaints post surgery as assessed by PFDI-20 Score was more in patients who underwent high uterosacral suspension patients. A study conducted by Bakisololo et al in 2018 showed that there was no improvement of colorectal -anal symptoms in both surgeries [9] . Similarly study of Silva et al revealed that that there was no benefit in bowel symptoms post vaginal uterosacral suspension [10] .…”
Section: Discussionmentioning
confidence: 93%
“…Patients's subjective assessment of quality of life post surgery was assessed using (i) pelvic floor distress inventory (PFDI-20) &(ii) pelvic floor impact Questionnaire. (PFIQ-7) [9] . Results: Out of 50 patients group I(sacrocolpopexy group) included 28 patients.…”
mentioning
confidence: 99%
“…We noticed that neither the patients of LSC group nor those of the LHUSL group were satisfied in the CRADI-8 and CRAIQ-7, thus indicating that the Colorectal-anal symptoms remained the same after both surgeries. A previous study from 2018 that compared the robotic-assisted uterosacral ligament suspension and the robotic-assisted sacrocolpopexy also did not find any statistical significance in bowel function [17].Similarly, a recent study using vaginal uterosacral ligament vault suspension did not find a significant improvement in bowel function [18].…”
Section: Discussionmentioning
confidence: 97%